The unruly tongue in early modern England : three treatises - Vienne-Guerrin, Nathalie (Fairleigh Dickinson University Press, 2012)
This volume excavates the biblical and classical sources behind three early modern treatises that denounce the numerous sins of the tongue that cause damage in the Elizabethan society.